2021
DOI: 10.14202/vetworld.2021.2346-2355
|View full text |Cite
|
Sign up to set email alerts
|

The first isolation and detection of Ornithobacterium rhinotracheale from swollen head syndrome-infected broiler flocks in Iraq

Abstract: Background and Aim: The swollen head syndrome (SHS) makes up complex diseases that infect the upper respiratory tract in poultry and causes several economic losses. Furthermore, this syndrome is considered one of the multifactorial etiological agents. Therefore, this study isolated and molecularly detected Ornithobacterium rhinotracheale (ORT) in poultry. Materials and Methods: This study was conducted at 67 broiler farms that had birds observed to be infected with the SHS from September 2018 until August 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Hassan et al. reported for the first time in Iraq that out of 67 broiler chickens with swollen head syndrome, 28 samples were positive for ORT (Al‐Hasan et al., 2021 ). This study showed the prevalence of ORT in commercial poultry flocks.…”
Section: Discussionmentioning
confidence: 99%
“…Hassan et al. reported for the first time in Iraq that out of 67 broiler chickens with swollen head syndrome, 28 samples were positive for ORT (Al‐Hasan et al., 2021 ). This study showed the prevalence of ORT in commercial poultry flocks.…”
Section: Discussionmentioning
confidence: 99%
“…The rolling infection of birds with vaccine viruses within a flock, when the initial coverage is incomplete, can lead to vaccination reactions, thus complicating diagnostic efforts [ 41 ]. Given the epidemiological context in Tunisia, an infection with a rolling IBV vaccine strain could be co-infected by H9N2 LPAIV which leads to the exacerbation of the clinical signs [ 42 , 43 ]. In this study, we report the detection of the GI-23 lineage (variant 2) for the first time in Tunisia.…”
Section: Discussionmentioning
confidence: 99%
“…In these co-infections, the major viral combinations were H9N2 + IBV (6/16) and H9N2 + aMPV (8/16). Several experimental studies have shown that co-infections with H9N2 LPAIV and IBV consistently result in more severe clinical signs than single infections with either H9N2 LPAIV or IBV, regardless of the virulence of the IBV strain [ 17 , 42 , 43 ]. This synergy between H9N2 LPAIV and IBV could be explained either by the severe inflammatory response induced by IBV [ 20 ], or by the trypsin-like serine protease encoded by IBV which probably facilitates the cleavage activation of the hemagglutinin of the H9N2 LPAIV virus, and thus increases its replication [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Mohd-Zain et al (2008) and Hegazy et al (2015) discovered three distinct isolates which were amoxicillin and doxycycline sensitive. In addition, Mayahi et al (2016), Hassan et al (2020) and Al-Hasan et al (2021) recorded that ORT strains were sensitive to florfenicol (100%), colistin (100%) and doxycycline (71.4%), respectively. On the other hand, Lanes 1, 2, 4, 5, 6, 7, 9, 10, 11, 12, 13 & 15 are positive samples (625bp).…”
Section: Discussionmentioning
confidence: 99%